Emerging interior architecture and design practices enabled by remote working: opportunities and challenges - Liew, Son Jiin (2023)
Working from home became popular throughout the pandemic. Many people had work responsibilities that couldn't be done remotely. Adoption of the remote working left employers unable to transfer workstations to home or build effective digital communication channels. Work-life balance and personal-professional boundaries have changed since moving from work to home. Changes in risk landscapes and contextual factors have also altered the workplace and subsequently made employer duties difficult to establish. This research aims to look into the opportunities and challenges of remote working in interior architecture and design for employers and employees. During the pandemic, a significant number of people switched to remote work; nevertheless, it is important to note that this change was not uniformly applicable, particularly for those with work duties that could not be done remotely. Employers were caught off guard by the rapid popularity of remote work, posing issues in seamlessly transferring offices to home and developing effective digital communication methods. Moreover, limited studies are dedicated to the opportunities and challenges of remote working in the interior architecture and design industry. Therefore, the research is carried out to determine the opportunities and challenges of remote working. There were a total of 80 respondents from the interior architecture and design field through distributing the questionnaire. Through the mean ranking test, the top five of opportunities were: (1) investing more time in family, pets, and friends; (2) increasing digital skill development; (3) increasing autonomy, flexibility, and empowerment; (4) contributing to carbon footprint reduction; and (5) using new digital tools to boost team collaboration. The top five of challenges were: (1) using new information technology systems and seeking assistance; (2) learning new digital tools and skills; (3) balancing work productivity, effectiveness, and self-development; (4) shifting mindset and culture from office to remote working; and (5) managing cognitive overload and exhaustion from multiple meetings in a row. Subsequently, the factor analysis was carried out to determine the underlying components, which were increasing digital transformation and workforce empowerment; integrating nature and physical activities into workdays; improving personal development and productivity; and increasing sustainable life enrichment for opportunities. The components for challenges of remote working were changing work settings; adapting to new technologies; committing to increased workloads and responsibilities; and adapting to remote dynamics. This research holds significant value for the interior architecture and design industry as it carefully examines and delineates both opportunities and challenges that arise during remote working, when the emerging practices. By focusing on these aspects, the findings of the research can provide valuable insights, guidance, and assistance to stakeholders within the industry, aiding in informed decision-making and fostering a proactive approach to navigating the evolving landscape.